The Use of Instagram Blog to Promote Students’ Writing Skill in Descriptive Text of English Tour and Travel - Putu Ngurah Rusmawan (PANYONARA: Journal of English Education, 2022)
Students’ in tourism business management vocational education program of Banyuwangi State Polytechnic must have excellent writing skill to promote tourist destination in Banyuwangi by writing a description of tourist destination in Instragram blog. This study aims to identify and to describe teaching learning process by using Instagram blog. This research used qualitative design. The researcher began to investigate the classroom online teaching and learning classroom activities by using several research instruments such as observation checklist, interview, and questionnaire. The lecturer tried to use Instagram blog as teaching aid during teaching and learning process especially in writing descriptive text about some popular tourist destinations in Banyuwangi. She also made them interested to begin write their idea. It could give the students a greater chance to write and express their ideas in English. This research was hold in Banyuwangi State Polytechnic on February 4th until 4th March, 2021. The result of this research was Instagram blog can help the lecturer taught well besides that the lecturer had already prepared learning contract well therefore she taught clearly.